(Re)Applying social psychology to organizational work, well‐being, and leadership. Issue 1 (10th December 2015) - Rast, David E.; Axtell, Carolyn; McGlynn, Stephen
Abstract: Research on organizational behavior is fundamentally an application of social psychology theory and phenomena. While much of organizational psychology is inherently grounded in social psychological research, these two disciplines are largely disconnected from one another. More visibility of the commonalities may encourage discussion, collaboration, and integration between these two fields—an integration that will only benefit each discipline. The present article briefly reviews the historic overlap between these disciplines, the resulting divide between them, and then discusses recent developments demonstrating the potential power of reconnecting social psychology with organizational‐relevant research. We then examine how the six empirical articles in this Special Issue benefit from applying social psychological theory to organizational research. We will conclude by identifying potential areas ripe for future research.